Al-Hallâj Sebagai Korban Politik atau Transgresor Teologi - Hodri Hodri (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2011)
The article attempts to reveal al-Hallâj’s history of thought that caused his death as he was considered an apostate who violated religious boundaries. Moreover, on several occasions, al-Hallâj was made as a sort of warning for those who “cheat” with religious issues will be firmly punished by the death penalty. It has been rarely clarified that Al-Hallâj was, in fact, a political victim by divulging religious issues as the main reason. As a concept, Hulûl, which becomes the main doctrine of al-Hallâj, has been often misunderstood and seen as conduct that leads to apostasy. The reason is that the death penalty executed its founder as he was accused of being an apostate. On the other side, such a view is not quite surprising since the level of understanding held by the majority of Muslims has, in fact, been within khitâbî level. It has caused them hard to properly and correctly understand such philosophical discourses as hulûl, ittihâd, or wahdat al-wujûd. This condition has been worsened by the fact that literature on al-Hallâj and hulûl, especially in the Indonesian language, is rare. After centuries, the idea of hulûl has been frequently misunderstood. However, careful study will show that hulûl, like other Sufi’s doctrines, is Sufism experience expression of al-Hallâj when he felt the presence of God, i.e., the encounter of human’s lâhût with God’s nâsût. Therefore, the execution of al-Hallâj has been based on more political interest than theological reason.